Ideology and discourse of Kurdish stories, stories of 1950 - 1969 for example - Mohammed Ahmed Hasan (Zanco Journal of Humanity Sciences)
The discourse of Kurdish fiction during the period 1950-1969 is unique in that ideology dominated the texts during this period. That is, stories have become a means of expressing the discourse of those stories. Our work in this study is to examine in what ways stories have been instrumentalized. At the same time, we have worked to illustrate the impact of ideology and content on the technique and art of storytelling. To do this, we have first presented the title as a main genre and an abbreviation of the text, in order to see how the titles have been sacrificed. The second aspect is working on the power of reality, that is, the stories convey reality in a vague way, without modifying reality, which is another aspect that neglects the art of storytelling. Ideology is another aspect that has adversely affected the content and technique of stories of that period. This ideology has killed the thinking of the characters and prevented them from expressing their reality and story. Finally, we present the results of the study in several points, along with a list of sources.